Frontispiece: Enantioselective Total Synthesis and Absolute Configuration Assignment of (+)‐Tronocarpine Enabled by an Asymmetric Michael/Aldol Reaction. Issue 10 (24th February 2020) - Tan, Dong‐Xing; Zhou, Jie; Liu, Chao‐You; Han, Fu‐She
Abstract : Natural Product Synthesis In their Communication on page 3834, F.‐S. Han et al. report the asymmetric total synthesis and absolute configuration determination of (+)‐tronocarpine. The [6.5.7.6.6] pentacyclic core was constructed by using a sequential cyclization strategy.